Fossil Gastropods From a Paleo-Indian Archaeological Site in Calgary, Alberta, Canada: Local and Regional Significance - Michael Wilson; Aurele La Rocque (Hello World!, 1973)
In November, 1968 salvage archaeological excavations were conducted at the Mona Lisa site (EgPm- 3 in the Canadian site numbering system) in Calgary, Alberta, Canada Excavations for the basement of an art gallery encountered an extensive bison bone bed underlying the Mazama volcanic ash, and associated crude artifacts indicated that man was the predatory agent involved (Wilson , 1969b).